2016
DOI: 10.18632/oncotarget.12746
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of the safety and pathogenicity of a live attenuated recombinant influenza A/H7N9 seed strain and corresponding MF59-adjuvanted split vaccine

Abstract: Developing a safe and effective H7N9 influenza vaccine was initiated in early spring 2013, following human infections with a novel avian influenza A (H7N9) virus. In this study, a candidate H7N9 vaccine seed strain is produced using reverse genetics, with HA and NA derived from a human H7N9 virus and the remaining genes from the PR8 backbone virus which grows well in eggs. We verified that the virulence and transmissibility of the recombinant H7N9 vaccine seed strain were decreased as compared to wild-type H7N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Moreover, we performed acute toxicity, repeated dose toxicity, and active systemic anaphylaxis tests to evaluate the safety of our H7N9 vaccine in mice. This vaccine completed the immunogenicity and safety testing [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we performed acute toxicity, repeated dose toxicity, and active systemic anaphylaxis tests to evaluate the safety of our H7N9 vaccine in mice. This vaccine completed the immunogenicity and safety testing [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Other H7N9 vaccine candidates have been tested in preclinical studies and have shown to be immunogenic and protective in animal models. These vaccines include H7N9 split vaccines using different adjuvants like SWE (an oil-in-water adjuvant) 26 and MF59 27 , 28 or non-adjuvanted split vaccines 29 . Other approaches are based on live attenuated virus vaccines 30 , 31 , recombinant H7 HA formulations 32 , or mRNA 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…All serum samples were treated with receptor destroying enzyme [ 9 ]. Prior to HI testing, a two-fold serial dilution series of serum was mixed 1:1 with four hemagglutinating units of virus (wild type H7N9 virus A/Zhejiang/DTID-ZJU01/2013 (H7N9)) and incubated at 37°C for 1 h. Subsequently, 50 μL 1% chicken erythrocytes were added, mixed, and incubated for 1 h at 4°C; all agglutination patterns were read within 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has the advantage of rapid preparation and rapid amplification. Accordingly, we verified that the recombinant clones harbor the desirable characteristics, including lower virulence and transmissibility, as a vaccine strain [ 9 ]. Additionally, the oil-in-water adjuvant MF59, which we have paired with our split virus vaccine, has been reported to be safe, well-tolerated, and able to improve the antibody response, permit dose sparing, and lower the antigen dose required to induce protection [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%